Breast epidermoid cyst: a case report - Dong, Xiaoxiao; Sun, Jian; Song, Dong; Ma, Jinxiu; Wang, Xiaozhen (Frontiers in Oncology, 2024)
An epidermoid cyst is a common benign skin lesion that can occur in any part of the body. However, epidermoid cysts occurring in the breast are extremely rare, rarely reported, and more prone to complications such as infection, rupture, and malignant alteration. Here, we report a case of a 50-year-old woman with a mammary epidermoid cyst. The patient noticed a mass of the left nipple during bathing. A puncture test was performed considering the epidermoid cyst. Moreover, local extended resection of the nipple and areola was performed. Postoperative pathological findings confirmed the diagnosis of a mammary epidermoid cyst. After 2 years of postoperative follow-up, the patient had no surgery-related complications and no signs of tumor recurrence.